Adaptive asymptotic tracking control of uncertain nonlinear systems with input quantization and actuator faults. (October 2016) - Li, Yuan-Xin; Yang, Guang-Hong
Abstract: This paper studies the problem of adaptive tracking control for a class of uncertain nonlinear systems with input quantization, external disturbances and actuator faults. It is assumed that the upper bounds of disturbances and the time varying stuck faults, are unknown. Firstly, an intermediate control law is designed by a modified adaptive backstepping design procedure, where a damping term with the estimate of unknown bounds and a positive time-varying integral function are introduced in the intermediate control law. Then, a novel smooth function is introduced in the control law to eliminate the effect of quantization based on the intermediate control law constructed in the first step. It is shown that all the closed-loop signals are bounded and the output tracking error converges to zero asymptotically in spite of input quantization, disturbances and possibly infinite number of faults. Finally, simulation results demonstrate the efficiency of the proposed algorithm.